2010
DOI: 10.5251/ajsms.2010.1.2.141.149
|View full text |Cite
|
Sign up to set email alerts
|

Variation factors of project plans and their contributions to project failure in Nigeria

Abstract: This study examines and analyses the variation factors of project plan and their contributions to project failure. The slippage of project plans with respect to budget, schedule and quality specifications are indicators of poor performance and imminent failure. The primary data used for the study were captured by field survey on some construction firms based on their experience and perceptions on the subject matter. The methods of multiple regression and correlation analyses were the analytical tools used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…11; projects located offshore Nigeria were completed on schedule and budget with no security or HSE incidents (Subsea, 2011 However, there are also less impressive records concerning the outcomes of other Nigerian projects. In the extant body of literature on project failure in Nigeria, Ubani, Nwachukwu and Nwokonkwo (2010) suggested that after the Nigerian independence in 1960, many developmental projects have suffered failure and abandonment. Okereke (2012) examined projects from various sectors in Nigeria and highlighted several shortcomings and achievements.…”
Section: An Appraisal Of Selected Projects In Nigeriamentioning
confidence: 99%
“…11; projects located offshore Nigeria were completed on schedule and budget with no security or HSE incidents (Subsea, 2011 However, there are also less impressive records concerning the outcomes of other Nigerian projects. In the extant body of literature on project failure in Nigeria, Ubani, Nwachukwu and Nwokonkwo (2010) suggested that after the Nigerian independence in 1960, many developmental projects have suffered failure and abandonment. Okereke (2012) examined projects from various sectors in Nigeria and highlighted several shortcomings and achievements.…”
Section: An Appraisal Of Selected Projects In Nigeriamentioning
confidence: 99%
“…These changes can lead to deviations from the sum stipulated in the contract [18]. Evidently, most construction projects especially in developing countries, usually suffer from cost and time overruns due to variations in project plans with the consequence of stagnated economic development [16,6]. This situation compels the need to mitigate detrimental variations during construction process of building projects, as the major instances of project cost and time overruns take place during construction phase.…”
Section: Detrimental Variations With Their Adverse Effectsmentioning
confidence: 99%
“…Ubani et al [6] identified engagement of project manager to manage the project, clarity of variation order procedures, control for variation orders to arise through contractual clauses and effective use of scheduling techniques as potential mitigation measures of detrimental variations in the Nigerian construction industry. In his research, Moghaddam [10] found that variation logic, variation justification and valuation of indirect effects of variations as significant mitigation measures in the Iranian construction industry.…”
Section: Mitigation Measuresmentioning
confidence: 99%
See 2 more Smart Citations